Non-Linear Mixed-Effects Pharmacokinetic Modeling of the Novel COX-2 Selective Inhibitor Vitacoxib in Cats - Wang, Jianzhong; Schneider, Benjamin K.; Xiao, Hongzhi; Qiu, Jicheng; Gong, Xiaohui; Seo, Yeon-Jung; Li, Jing; Mochel, Jonathan P.; Cao, Xingyuan (Frontiers in Veterinary Science, 2020)
The objective of this study was to develop a nonlinear mixed-effects (NLME) model to describe the disposition kinetics of vitacoxib in cats following intravenous (I.V) and oral (P.O) (single and multiple) dosing. Data from 6 consecutive studies with sixteen healthy neutered domestic short hair cats were pooled together to build a pharmacokinetic (PK) model using NLME. Population pharmacokinetic parameters were estimated using the stochastic approximation expectation maximization (SAEM) algorithm implemented in Monolix 2019R2. A two-compartment mammillary disposition model with simultaneous 0 and 1st order absorption best described the PK of vitacoxib in plasma after oral dosing. The systemic CL of vitacoxib was found to be low (110 mL/h), with a steady state volume of distribution (VSS) of 3.42 L in cats. Results from the automated covariate search in Monolix 2019R2 showed that bodyweight had a significant effect on the central volume of distribution of vitacoxib. Lastly, using Monte Carlo simulations, we investigated the time-course of several dosages of vitacoxib from 0.01 to 8 mg/kg. Using this simulation set, we found a range of reasonable dosages which produce therapeutic plasma concentrations of vitacoxib for 24 hours or more in cats.